Actoprotector activity of 4-R-(ideneamino)- 5-R-4Н-1,2,4-triazole-3-thiols - Hlazunova, T. V.; Panasenko, O. I.; Knysh, Ye. H.; Глазунова, Тетяна Вікторівна; Панасенко, Олександр Іванович; Книш, Євгеній Григорович (My University, 2019)
In this study, actoprotector activity of 1,2,4-triazole derivatives is described. The biological activity of synthetic 4-R-(ideneamino)-5-R-4Н-1,2,4-triazole-3- thiols was analyzed. The forced swim test with a weight load of 10% of the test animal’s body weight was applied. According to the obtained results, compounds that contained NH4+ and CuSO4 substituents were among the most active, potency of which was close to that of the reference drug Riboxin. Introduction of propylamine, isopropylamine and piperazine groups into the molecule decreases the actoprotector activity. Compounds containing monoethanolamine, diethylamine, ethylamine, and magnesium sulfate moieties almost did not exhibit actoprotector activity.
Keywords: actoprotector activity; 1,2,4-triazole derivatives; structure-activity